2017
DOI: 10.1186/s12939-017-0667-y
|View full text |Cite
|
Sign up to set email alerts
|

An economy-related equity analysis of health service utilization by women in economically underdeveloped regions of western China

Abstract: BackgroundThe Chinese government has long been committed to eliminating the inequality in the utilization of health services; however, it still lacks an analysis or measurement of the economy-related inequality in the utilization of women’s health services.MethodsThe economy-related utilization of health services in women aged 15 years and above was assessed by the horizontal inequity index of a two-week outpatient rate and annual inpatient rate from the 5th National Health Service Survey of Shaanxi Province. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 30 publications
4
43
2
1
Order By: Relevance
“…Present studies have shown that household income is beneficial to the use of inpatients in the rich, which is the dominant determinant of inequality in the utilization of inpatient services since more wealthy individuals are able to pay for and utilize more inpatient services [37][38][39]. But some studies have shown that the differences of health service utilization between income groups were not significant [40].…”
Section: Discussionmentioning
confidence: 96%
“…Present studies have shown that household income is beneficial to the use of inpatients in the rich, which is the dominant determinant of inequality in the utilization of inpatient services since more wealthy individuals are able to pay for and utilize more inpatient services [37][38][39]. But some studies have shown that the differences of health service utilization between income groups were not significant [40].…”
Section: Discussionmentioning
confidence: 96%
“…We speculate that social factors may also be related to this finding. As income increases, females tend to be more attentive than males to personal health management [38,43], make better use of health facilities and adopt healithier lifestyles [44] which all may lower hypertension risks. Due to the perception of beauty, affluent Chinese women are more attentive to appearance and value slenderness [45], thus more aware of a healthy diet and engage in more physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…To some extent, the inconformity indirectly reflected that the prevalence rate of malignant tumor continuously increased. With the development of economy, the per capita disposable income and health awareness of residents increased so that the residents would go to hospital when they were ill [19,20]. In addition, the unceasing improvement of NRCMS promoted the participation rate increasing which also resulted in the rise of hospital admissions [21,22].…”
Section: Discussionmentioning
confidence: 99%